Digital Literacy on the Use of E-Module towards Students’ Self-directed Learning on Learning Process and Outcomes Evaluation Cources - Sanova, Aulia; Bakar, Abu; Afrida, Afrida; Kurniawan, Dwi Agus; Aldila, Febri Tia (Jurnal Pendidikan Indonesia, 2022)
The context of learning in the 4.0 revolution era is currently a challenge, especially in the world of education at the university level. The creative learning process needs to be developed so that learning patterns need to be updated by placing students as learning subjects (student-centered learning) and applying more flexible learning media in accordance with technological advances in the field of education to develop student abilities. The use of e-modules is one type of e-resources that can be accessed and displayed using computer-based media as an alternative choice by students in obtaining lecture materials and learning processes independently. This study aims to determine the level of closeness of the relationship and see whether or not there is a simultaneous (together) and partial effect between digital literacy and student self-directed learning. This research leads to quantitative research. The results showed that there was a correlation of 0.705 and had a simultaneous effect of 0.000 < 0.005 with a calculated Fcount of 31.71 > Ftable 3.32 and tcount = 5.631 > ttable = 1.69092. It can be concluded that there is a strong correlation level and has a simultaneous and partial influence between digital literacy and students' self-directed learning on the use of the e-module on learning process and outcomes evaluation courses.